Assessing the effect of piezoelectric ultrasonic scaler tip wear on root surface roughness under influence of various working parameters: A profilometric and atomic force microscopic study - Atul Parashar; Neeta Bhavsar (Wolters Kluwer Medknow Publications, 2023)
Background: Assessing the effect of scaler tip wear on the root surface roughness using piezoelectric ultrasonic scaling device under influence of various working parameters, i.e. power setting, lateral force, and instrumentation time. Materials and Methods: An experimental study was conducted using 160 single-rooted tooth samples divided into two groups of new (n = 80) and worn tips (n = 80). Samples were prepared to examine the root surface roughness after being instrumented by new and worn piezoelectric ultrasonic tips (8 new/8 worn) at different parameters. The erosion ratio (ER) of the new/worn tip was examined under an atomic force microscope and roughness over root surface was measured by a contact surface profilometer. One-way analysis of variance test, post hoc Tukey's test, and independent t-test were used for intragroup, pair-wise multiple comparisons and intergroup comparison of average roughness (Ra) value. Results: A statistically significant difference was found between the ER of new and worn scaler tips (P < 0.001). Intragroup comparison between subgroups 1 and 8 showed a higher Ra value in both the groups (P < 0.005). There was a significantly higher Ra value of worn tips compared to new tips (P < 0.05). Significantly higher mean Ra value was shown when lateral force changed from 50 g to 100 g (P < 0.005). Conclusions: Increasing value of power setting, lateral force, and instrumentation time caused more surface roughness in worn-out scaler tips compared to new scaler tips. Lateral force and instrumentation time proved to be a major factor influencing surface roughness.